Evaluasi desain pendidikan terpadu pondok pesantren: Studi nilai kebangsaan dengan kemandirian ekonomi - Supriadi, Sudawan; Santoso, Ridwan; Wahyuni, Sri; Sasih, Agustin Wela; Yuanda, Femas; Qowi, Azhi Ridho Al (Proceedings Academic Universitas Jambi, 2025)
This study aims to evaluate the implementation of integrated education in Islamic boarding schools that instill the importance of national values ​​and economic independence among students. This study was conducted with 3 key informants and 40 research respondents. The research design followed a case study research approach. The results of this study prove that the implementation of integrated education has been carried out well in Islamic boarding schools, especially Al-Muhajirin Islamic boarding school. The results show that national values ​​are internalized through formal and non-formal activities in routine flag ceremonies, national holiday commemorations, and NU education within the Islamic boarding school environment. This is proven to significantly contribute to the success of integrated education (R = 0.624; R² = 0.390; p < 0.001). Meanwhile, economic independence is strengthened through the management of Islamic boarding school business units (laundry, cooperatives, agriculture, animal husbandry, workshops, and laser cutting services) as well as project-based entrepreneurship development that improves technical skills, creativity, and responsibility. Correlation analysis shows a perfect relationship between integrated education and economic independence (p < 0.001). This finding confirms that the synergy between strengthening national values ​​and developing economic independence within an integrated educational framework effectively produces students who are noble, independent, and adaptive to the development of the times, while simultaneously strengthening the role of Islamic boarding schools as centers for character education and community-based economic empowerment.